2020
DOI: 10.2196/18251
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Quadri-Planes Method in Computer-Aided Diagnosis of Breast Lesions by Ultrasonography: Prospective Single-Center Study

Abstract: Background Computer-aided diagnosis (CAD) is a tool that can help radiologists diagnose breast lesions by ultrasonography. Previous studies have demonstrated that CAD can help reduce the incidence of missed diagnoses by radiologists. However, the optimal method to apply CAD to breast lesions using diagnostic planes has not been assessed. Objective The aim of this study was to compare the performance of radiologists with different levels of experience wh… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 27 publications
1
7
0
Order By: Relevance
“…S‐Detect is a CAD software that can realize automatic segmentation and analysis of US morphological descriptions and generate the decisions automatically. In previous studies on the diagnostic efficiency of S‐Detect software for breast lesions, most of them take BI‐RADS 4a (benign, 3 or lower) as the cutoff value, 16–20 and two studies take BI‐RADS 4b (benign, 4a or lower) as the cutoff value 22,31 . BI‐RADS 4a lesions mainly include some atypical benign and malignant lesions, with a malignant rate of 2–10% 8 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…S‐Detect is a CAD software that can realize automatic segmentation and analysis of US morphological descriptions and generate the decisions automatically. In previous studies on the diagnostic efficiency of S‐Detect software for breast lesions, most of them take BI‐RADS 4a (benign, 3 or lower) as the cutoff value, 16–20 and two studies take BI‐RADS 4b (benign, 4a or lower) as the cutoff value 22,31 . BI‐RADS 4a lesions mainly include some atypical benign and malignant lesions, with a malignant rate of 2–10% 8 .…”
Section: Discussionmentioning
confidence: 99%
“…At present, some studies have confirmed the feasibility of S‐Detect in differentiating breast masses 15–17 . Some studies have compared the diagnostic performance between S‐Detect and radiologists with different experiences 16–22 . A few studies have explored the value of S‐Detect in reducing unnecessary biopsy of experienced 23 and less experienced radiologists 21 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This study demonstrated the feasibility of using a mobile app to monitor the recovery status of patients with drains and to assist patients and caregivers in detecting abnormalities in a timely manner. Remote apps could support self-care and allow close follow-up [32][33][34]. We also identified an unexpected reduction in the rates of hospital return and readmission in the SurgCare group (6.4%) compared with the conventional group (25.9%) (P=.02).…”
Section: Discussionmentioning
confidence: 81%
“…Deep learning (DL) is a subset of machine learning that uses an advanced form of artificial neural networks; the use of DL has impacted health care [1,2]. Numerous applications of DL in medicine, such as computer-aided diagnosis, have been studied [3][4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%